2009
DOI: 10.1017/s0022149x09336408
|View full text |Cite
|
Sign up to set email alerts
|

A review on swimmer's itch and the occurrence of bird schistosomes in Iceland

Abstract: In the past decade, swimmer's itch (SI) has repeatedly occurred in people who have been wading or bathing in ponds or lakes in Iceland where water birds and snails are abundant. Some of the affected sites were warmed by geothermal activity, and others were not. A search for the causative agent of SI, ocellate furcocercariae that have been found in Iceland only in Radix peregra snails, revealed an average infection prevalence of 1.4% (n = 12,432). Locally, infection rates commonly exceeded 6%, the highest value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 15 publications
2
34
0
1
Order By: Relevance
“…Now it is re-confirmed that R. peregra, besides R. lagotis and R. labiata, can play a role as a vector of T. regenti; this is in agreement with the results from France (Jouet et al 2008). Interestingly, in Iceland, R. peregra represents the dominant snail species and hosts several schistosomes (Skírnisson et al 2009), showing that both the schistosomes and the snails can adapt to each other under specific local conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Now it is re-confirmed that R. peregra, besides R. lagotis and R. labiata, can play a role as a vector of T. regenti; this is in agreement with the results from France (Jouet et al 2008). Interestingly, in Iceland, R. peregra represents the dominant snail species and hosts several schistosomes (Skírnisson et al 2009), showing that both the schistosomes and the snails can adapt to each other under specific local conditions.…”
Section: Discussionsupporting
confidence: 85%
“…In North America and Europe, where most of the research has been focused, outbreaks occur in recreational ponds and reservoirs. These outbreaks have been reviewed extensively (7,8,70,71). Species of Trichobilharzia have been reported to cause dermatitis from other areas as well, such as Rwanda-Burundi (72), South Africa (73,74), New Zealand and Australia (75)(76)(77)(78)(79), Malaysia/Indonesia (80)(81)(82), Iran (65,(83)(84)(85)(86), United Arab Emirates (66), Thailand (87), and China (88,89) in the Eastern Hemisphere and Argentina (57,90,91), Chile (11), and El Salvador (92) in the Western Hemisphere.…”
Section: Diversity Of Schistosomes Causing Dermatitismentioning
confidence: 99%
“…For example, the accelerated growth of both snail and trematode larval populations (71) or changes in phenology of aquatic migratory birds to sedentary (268)(269)(270) can increase chances for outbreaks of cercarial dermatitis in both space and time.…”
Section: Ecological Factors Influencing the Occurrence Of Avian Schismentioning
confidence: 99%
See 2 more Smart Citations